2015
DOI: 10.1039/c4an02106a
|View full text |Cite
|
Sign up to set email alerts
|

Highly selective colorimetric bacteria sensing based on protein-capped nanoparticles

Abstract: A rapid and cost-effective colorimetric sensor has been developed for the detection of bacteria (Bacillus subtilis was selected as an example). The sensor was designed to rely on lysozyme-capped AuNPs with the advantages of effective amplification and high specificity. In the sensing system, lysozyme was able to bind strongly to Bacillus subtilis, which effectively induced a color change of the solution from light purple to purplish red. The lowest concentration of Bacillus subtilis detectable by the naked eye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 37 publications
0
26
1
Order By: Relevance
“…A chromogenic reaction occurs once the galactose moiety is cleaved by β-galactosidase. Qiu et al [ 34 ] reported that the lysozyme-capped Au nanoparticle’s colorimetric sensing system enabled the naked-eye detection of about 3.7 log CFU/mL of Bacillus subtilis suspended inside a 3-( N -morpholino)-propanesulfonic acid (MOPS) buffer. They also concluded that their colorimetric sensor is applicable for the rapid and specific microbial detection assay of complex samples.…”
Section: Colorimetric Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A chromogenic reaction occurs once the galactose moiety is cleaved by β-galactosidase. Qiu et al [ 34 ] reported that the lysozyme-capped Au nanoparticle’s colorimetric sensing system enabled the naked-eye detection of about 3.7 log CFU/mL of Bacillus subtilis suspended inside a 3-( N -morpholino)-propanesulfonic acid (MOPS) buffer. They also concluded that their colorimetric sensor is applicable for the rapid and specific microbial detection assay of complex samples.…”
Section: Colorimetric Methodsmentioning
confidence: 99%
“…Although the aforementioned studies demonstrated cost effectiveness, simplicity, ease of operation, and the rapid response of the colorimetric sensor, significant weaknesses and limitations were also observed. First and foremost, the researchers [ 32 , 33 , 34 ] suspended their target microorganisms in buffer or water. These solutions are typically cleaner and less complex than food homogenates.…”
Section: Colorimetric Methodsmentioning
confidence: 99%
“…The attachments (or detachments) of specific proteins to (or from) AuNP in the presence of competing interactions with target analytes can be monitored using color transitions of test solutions. For example, a facile method for detecting Bacillus subtilis was developed using AuNP complexed with lysozyme, which normally imparts a purple color [51]. Furthermore, lysozyme has selective affinity for peptidoglycans of gram-positive bacterial cell walls.…”
Section: Gold Nanoparticlesmentioning
confidence: 99%
“…Detection of Bacillus subtilis using gold nanoparticle/lysozyme supramolecules.Reproduced with permission from The Royal Society of Chemistry[51].…”
mentioning
confidence: 99%
“…Recently, considerable efforts have been devoted to the detection of protein by homogeneous assays, such as colorimetric assays based on various nanomaterials including gold nanoparticles, carbon nanotubes, metal nanocomposites, and carbon nanoparticles . These mix‐and‐measure techniques that have no need for separation steps significantly simplify operation and enhance the detection efficiency …”
Section: Introductionmentioning
confidence: 99%